Antimalarial Activities of Aminooxy Compounds - Berger, Bradley J. (American Society for Microbiology, 2000)
Twenty-three aminooxy compounds have been examined for their ability to inhibit the growth of the malaria parasite Plasmodium falciparum in vitro. Eight of these compounds were found to have 50% inhibitory concentrations less than 10 μM, with the best drugs being canaline (the aminooxy analogue of ornithine) and CGP51905A at 297 ± 23.6 nM and 242 ± 18.8 nM, respectively. Canaline was also assayed in combination with the ornithine decarboxylase inhibitor difluoromethylornithine, and the two drugs were found to be synergistic in antimalarial activity.